Tanzania - Sustaining and Sharing Economic Growth : Country Economic Memorandum and Poverty Assessment, Volume 2. Main Report - World Bank (Washington, DC, 2012)
Tanzania's National Strategy for Growth and Reduction of Poverty (NSGRP) sets an ambitious target of 6 to 8 percent annual economic growth to achieve rapid reduction in poverty. This report focuses on three issues that are central to the success of Tanzania's poverty reduction efforts: 0 what factors explain Tanzania's recent acceleration in economic growth; has the accelerated economic growth translated into reduced poverty; and what must be done to sustain economic growth that is pro-poor. The report presents evidence from the macroeconomic, sectoral, and firm and household levels that shed light on these questions. The report is presented in two volumes. Volume I summarizes the main findings and recommendations. Volume II contains the main report.